Fluid Retention over the Menstrual Cycle: 1-Year Data from the Prospective Ovulation Cohort. (8th August 2011) - White, Colin P.; Hitchcock, Christine L.; Vigna, Yvette M.; Prior, Jerilynn C.
Abstract : We report menstrual and mid-cycle patterns of self-reported "fluid retention" in 765 menstrual cycles in 62 healthy women. Self-reported "fluid retention, " commonly described as bloating, is one element of the clinical assessment and diagnosis of premenstrual symptoms. These daily diary data were collected as part of an observational prospective one-year study of bone changes in healthy women of differing exercise characteristics. Ovulation was documented by quantitative basal temperature analysis, and serum estradiol and progesterone levels were available from initial and final cycles. Fluid retention scores (on a 0–4 scale) peaked on the first day of menstrual flow (mean ± SE :0.9 ± 0.1 ), were lowest during the mid-follicular period, and gradually increased from0.22 ± 0.05 to0.50 ± 0.09 over the 11 days surrounding ovulation. Mid-cycle, but not premenstrual, fluid scores tended to be lower in anovulatory cycles (ANOVAP = 0.065 ), and scores were higher around menstruation than at midcycle (P < 0.0001 ). Neither estradiol nor progesterone levels were significantly associated with fluid retention scores. The peak day of average fluid retention was the first day of flow. There were no significant differences in women's self-perceived fluid retention between ovulatory and anovulatory cycles.